2020
DOI: 10.1097/j.pain.0000000000001900
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality: physiological and behavioral mechanisms to increase individual pain tolerance limits

Abstract: Immersive virtual reality (VR) consists of immersion in artificial environments through the use of real-time render technologies and the latest generation devices. The users feel just as immersed as they would feel in an everyday life situation, and this sense of presence seems to have therapeutic potentials. However, the VR mechanisms remain only partially known. This study is novel in that, for the first time in VR research, appropriate controls for VR contexts, immersive characteristics (ie, control VR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 52 publications
7
37
0
5
Order By: Relevance
“…VR and AR-based interventions have been found to be effective in reducing acute pain from medical procedures associated with transient pain (eg, distraction) among adults [ 1 - 3 ] and youth [ 1 , 4 - 6 ]. In this context, the effectiveness of VR arises from its ability to provide multisensorial engagement that can compete with pain signaling while also eliciting enjoyment and decreasing anxiety and negative mood [ 7 ]. Youth are particularly well suited to benefit from VR and AR-based pain interventions given their facility with technology and the ease with which they can engage in imaginative experiences [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…VR and AR-based interventions have been found to be effective in reducing acute pain from medical procedures associated with transient pain (eg, distraction) among adults [ 1 - 3 ] and youth [ 1 , 4 - 6 ]. In this context, the effectiveness of VR arises from its ability to provide multisensorial engagement that can compete with pain signaling while also eliciting enjoyment and decreasing anxiety and negative mood [ 7 ]. Youth are particularly well suited to benefit from VR and AR-based pain interventions given their facility with technology and the ease with which they can engage in imaginative experiences [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout each condition, we recorded electrocardiograms to obtain heart rate variability (HRV) measures to explore whether pain modulation by cognitive load would be associated with changes in HRV. We had no clear hypothesis about the direction of the association: while a recent study by Colloca et al (21) reported that decreased pain sensitivity in a relaxing VR environment correlated with higher HRV, pain relief by cognitive distraction has been associated with decreased HRV (22), which is consistent with studies that have linked higher mental stress to lower HRV (23,24). In the present study, we wanted to assess whether changes in HRV would also reflect changes in pain thresholds in a more cognitively challenging VR environment.…”
Section: Introductionmentioning
confidence: 89%
“…For example, immersive virtual reality, rst reported by our team in the 1990s [24], is emerging as an unusually powerful adjunctive non-pharmacologic analgesic. [6,9,15,21,26,34,36,39,40,42,47,48,49,62,70] fMRI brain scans show that in addition to reducing participants subjective experience of pain, VR also reduces painrelated brain activity. [29] A follow up fMRI study showed that VR reduces pain as much as a moderate dose of hydromorphone.…”
Section: Introductionmentioning
confidence: 99%